International Visegrad project: How to prevent SMEs from failure - actions based on comparative analysis in Visegrad countries and Serbia - Mihajlović, Ivan; Milošević, Isidora; Stojanović, Anđelka (Serbian Journal of Management, 2019)
This issue of Serbian Journal of Management (SJM 14(2) 2019), is dedicated to one very important challenge of contemporary entrepreneurship, that is condensed in single question: How to prevent SMEs from failure ? The articles published in this issue are all addressing different aspects of entrepreneurial activities that can lead to successful and/or unsuccessful operations. Part of the articles pubished in this issue are directly presenting the results of the project: HOW TO PREVENT SMEs FROM FAILURE (Actions based on comparative analysis in Visegrad countries and Serbia), which was financially supported by the International Visegrad Fund. During the projects, researchers from all four Visegrad group countries, as well as researchers from Serbia, were analysing SMEs from their regions, which suffered from some degree of financial distress or have failed in the past. The main purpose of this investigation was to analyse and identify the most important business factors that can lead to failure of the SMEs businesses. Obtained results are presented in this issue. On the other hand, part of the manuscripts in this issue are invited from the authors who are also investigating the SMEs operation and are dealing the factors of success of the entrepreneurial activities, in the region outside Visegrad group or Serbia. The main motive of this issue is to address this highly important challenge - SMEs successful operations.